2017
DOI: 10.3892/etm.2017.4840
|View full text |Cite
|
Sign up to set email alerts
|

Gypenosides induce cell death and alter gene expression in human oral cancer HSC-3 cells

Abstract: Gypenosides (Gyp), the primary components of Gynostemma pentaphyllum Makino, have long been used as a Chinese herbal medicine. In the present study, the effects of Gyp on cell viability, the cell cycle, cell apoptosis, DNA damage and chromatin condensation were investigated in vitro using human oral cancer HSC-3 cells. The results of the present study indicated that Gyp induces cell death, G2/M phase arrest and apoptosis in HSC-3 cells in a dose-dependent manner. It was also demonstrated that Gyp decreased the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Finally, sub-fraction GPE 15 was subjected to a semipreparative HPLC column (SHIM-pack PREP-ODS(L) 250×50 mm) and eluted with 47% acetonitrile in water at a flow rate of 5 mL/min to produce compounds 1, 2, and 3. The structures of the compounds were characterized by 1 H-NMR, 13 C-NMR, and LC-MS as GL, GLI, and Rg3 spectra (S1). NMR data were consistent with that of the reference [5,26], and the compounds were eventually identified as GL, GLI, and Rg3 (Figure 1).…”
Section: Isolation and Purification Of Gl Gli And Rg3 From Gpementioning
confidence: 99%
See 2 more Smart Citations
“…Finally, sub-fraction GPE 15 was subjected to a semipreparative HPLC column (SHIM-pack PREP-ODS(L) 250×50 mm) and eluted with 47% acetonitrile in water at a flow rate of 5 mL/min to produce compounds 1, 2, and 3. The structures of the compounds were characterized by 1 H-NMR, 13 C-NMR, and LC-MS as GL, GLI, and Rg3 spectra (S1). NMR data were consistent with that of the reference [5,26], and the compounds were eventually identified as GL, GLI, and Rg3 (Figure 1).…”
Section: Isolation and Purification Of Gl Gli And Rg3 From Gpementioning
confidence: 99%
“…A research study by Yun et al has demonstrated that gypenosides could be utilized to promote weight loss as it regulated fat metabolism without causing side effects, such as diarrhea or altered appetite [29]. Other studies have found that G. pentaphyllum extract acted against various diseases and possessed hypoglycemic [13], immunomodulating [14], cholesterol-lowering [15], antioxidant [16], and other activities. The dammarane saponins isolated from G. pentaphyllum, specifically gypenosides, have served as economically important raw materials for the food and pharmaceutical industries.…”
Section: Increased Ampk-dependent Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Feng et al ( 19 ) reported that miR-204-5p upregulation promoted the recovery of the upper and lower limb strength in mice with SCI by affecting the levels of the inflammatory cytokines, Toll-like receptor (TLR)4 and inducible nitric oxide synthase (iINOS), by targeting SRY-Box transcription factor 11 (SOX11). Recently, several studies have revealed that gypenosides have the potential to modulate miRNA expression in various cancer cells ( 20 - 22 ). Against this background, the present study examined whether miRNAs are involved in the therapeutic effects of GP-17 on SCI.…”
Section: Introductionmentioning
confidence: 99%
“…G. pentaphyllum has been reported to exert anti-inflammatory, lipid metabolism-regulatory, anti-diabetic, neuroprotective, and anti-obesity effects [ 20 21 22 23 24 25 26 27 34 ]. Gypenosides are a class of major bioactive compounds in GPE and have been evaluated for their beneficial cholesterol-lowering, antioxidant, hypoglycemic, and tumor-suppressive effects [ 44 45 46 47 ]. Gypenosides or polysaccharides from G. pentaphyllum help improve exercise tolerance, extend swimming time, prevent the rise in lactate levels, and mitigate oxidative stress during exhaustive exercise [ 32 33 ].…”
Section: Discussionmentioning
confidence: 99%